EFFECTS OF PROPRIOPCEPTIVE INTERVENTIONS ON ANKLE SPRAINS IN ATHLETES: EMPHASIS ON RECURRENCE, CHRONIC INSTABILITY, AND IMPROVED PROGNOSIS (REMUNOM, 2025)
Considering the importance and frequency of ankle sprain injuries in sports, the main objective of this study is to investigate the effects of proprioceptive interventions in the prevention of ankle sprains in athletes, focusing on their effectiveness in reducing recurrence and promoting joint stability. To this end, a systematic review of the literature was conducted, based on scientific articles published between 2015 and 2025 in the PubMed, SciELO, and BVSALUD databases. The selected studies included different proprioceptive training protocols, such as exercises on unstable surfaces, proprioceptive neuromuscular facilitation (PNF), and other approaches focused on balance. The results point to the effectiveness of these interventions in improving balance, proprioception, and function, in addition to a significant reduction in the recurrence rate of sprains and the time required to return to sports activities. It is concluded that the application of proprioceptive protocols is an effective and safe strategy, especially when combined with other therapeutic approaches, and is recommended for both rehabilitation and prevention of ankle sprains in athletes.